Occurrence of subnormal size phenotype in the latest Eifelian/earliest Givetian boundary, Tibagi city, Paraná State, Brazil: taphonomic and paleosynecologic implications - Bosett, Elvio Pinto; Horodysk, Rodrigo Scalise; Zabini, Carolina; Matsumura, Willian Mikio Kurita; Penteado, Andressa Carla (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2010)
Subnormal size phenotype of marine invertebrates is recorded at the interval Neo-Eifelian/eo-Givetian (Devonian). These fossils represent a relictual fauna that resulted from a biotic crisis. Specific analysis were done to exclude the possibility of taphonomic bias. According with the taphonomic signatures obtained there was no significant bioclastic transport, and the taphocoenosis can be considered autochthonous to parautochthonous. The occurrence of subnormal size phenotype in the São Domingos Formation is not the result of bias and the data obtained evidences a real adaptative response for the stress conditions of the post-event syndrome (KACAK Event).
Keywords: Devonian; Malvinokaffric Realm; São Domingos Formation; Subnormal size phenotype; Taphonomy